Policing, Public Health, and Human Rights in India’s Conflict-Affected Regions: An Empirical Inquiry of Policing Practices - Srivastava, Roshni; Ruma, Kulsoom; Gupta, Ashmita; Jaiswal, Gautam; Dwivedi, Aniket (Journal of Neonatal Surgery, 2024)
Policing in conflict zones poses unique challenges that necessitate a delicate balance between maintaining security and safeguarding human rights. The chapter provides a comprehensive analysis of the operational difficulties, human rights issues, and security dilemmas faced by police officers, based on first-hand insights from serving officers.It begins with an overview of the conflict zones, offering historical and socio-political context. The roles and responsibilities of police officers in these areas are examined, including their efforts to maintain public order, prevent violence, and build community relations. The chapter delves into human rights challenges, including cases of alleged violations and the legal frameworks governing police conduct. Additionally, it analyses security dilemmas, such as the tension between stringent security measures and human rights protections.